Cardiomyocyte-fibroblast crosstalk in the postnatal heart - Uscategui Calderon, Maria; Gonzalez, Brittany A.; Yutzey, Katherine E. (Frontiers in Cell and Developmental Biology, 2023)
During the postnatal period in mammals, the heart undergoes significant remodeling in response to increased circulatory demands. In the days after birth, cardiac cells, including cardiomyocytes and fibroblasts, progressively lose embryonic characteristics concomitant with the loss of the heart’s ability to regenerate. Moreover, postnatal cardiomyocytes undergo binucleation and cell cycle arrest with induction of hypertrophic growth, while cardiac fibroblasts proliferate and produce extracellular matrix (ECM) that transitions from components that support cellular maturation to production of the mature fibrous skeleton of the heart. Recent studies have implicated interactions of cardiac fibroblasts and cardiomyocytes within the maturing ECM environment to promote heart maturation in the postnatal period. Here, we review the relationships of different cardiac cell types and the ECM as the heart undergoes both structural and functional changes during development. Recent advances in the field, particularly in several recently published transcriptomic datasets, have highlighted specific signaling mechanisms that underlie cellular maturation and demonstrated the biomechanical interdependence of cardiac fibroblast and cardiomyocyte maturation. There is increasing evidence that postnatal heart development in mammals is dependent on particular ECM components and that resulting changes in biomechanics influence cell maturation. These advances, in definition of cardiac fibroblast heterogeneity and function in relation to cardiomyocyte maturation and the extracellular environment provide, support for complex cell crosstalk in the postnatal heart with implications for heart regeneration and disease mechanisms.